First Report of blaIMP–4 and blaSRT–2 Coproducing Serratia marcescens Clinical Isolate in China - Huang, Xiangning; Shen, Siquan; Shi, Qingyu; Ding, Li; Wu, Shi; Han, Renru; Zhou, Xun; Yu, Hua; Hu, Fupin (Frontiers in Microbiology, 2021)
Carbapenemase-resistant Enterobacterales (CRE) has become a major therapeutic concern in clinical settings and carbapenemase genes have been widely reported in various bacteria. In Serratia marcescens, class A group carbapenemases including SME and KPC were mostly identified. However, there are few reports of metallo-β-lactamases-producing S. marcescens. Here, we first isolated a strain of an IMP-4-producing S. marcescens (S378) from a patient with urinary tract infection in China. The species were identified using MALDI-TOF MS and carbapenemase-encoding genes were detected using PCR and DNA sequencing. The results of antimicrobial susceptibility testing by broth microdilution method indicated that the isolate S378 was resistant to meropenem (MIC = 32μg/ml) and imipenem (MIC = 64μg/ml) and intermediate to aztreonam (MIC = 8μg/ml). The complete genomic sequence of S. marcescens was identified using Illumina (Illumina, San Diego, CA, USA) short-read sequencing (150bp paired-end reads), five resistance genes had been identified, including blaIMP-4, blaSRT-2, aac(6')-Ic, qnrS1 and tet(41). Conjugation experiments revealed that the plasmid was transferrable from donor to recipient. Complete sequence analysis of the plasmid pS378P bearing blaIMP-4 revealed that it was a 48,780 bp IncN type plasmid with an average GC content of 50% and was nearly identical to pP378-IMP (99% nucleotide identity and query coverage).